Correction to: HSPB7 gene polymorphism associated with anthropometric parameters of obesity and fat intake in a Central European population - Pavlová, Tereza; Novák, Jan; Zlámal, Filip; Dobrovolná, Julie (Central European Journal of Public Health, 2019)
We would like to submit the following correction to our recently published paper due to an error in the Table 2. The corrected table is given below.